New synonymies in the order Urodela Duméril, 1805 (Amphibia, Batrachia), with comments on the use of the formula "new taxon" to designate new nomina - Dubois, Alain (Zootaxa, 2012)
Dubois & Raffaëlli (2012) recently published a new comprehensive taxonomy and nomenclature of the recent salamanders and newts of the world. Almost coincidentally, Wake (2012) published a revised classification of the salamander family Plethodontidae. Three family-series (or family-group) nomina (scientific names) were proposed as new in both papers. According to the date appearing in Zootaxa, the latter paper was published on 18 September 2012, whereas, according to the printer Frédéric Paillart (personal communication), the former was mailed to subscribers of Alytes on 24 October 2012. Therefore the new nomina that are common to both papers are valid in the latter, and invalid junior synonyms and homonyms in the former. I here present complete synonymic lists for these three nomina, as well as a few additional comments.